(untitled) (International Journal of Engineering and Computer Science, 2016)
Internet of Things is a collection of entities which can be physical devices, animals, people ,electronic devices etc. If they are connected through a network they can exchange data without any human - human or human - computer interaction. 2011 hype cycle says that there is IoT for more than 10 years .So the need of an efficient protocol is of greater importance. Analysis says that there will be 20 billion connected devices in the year 2020. So these devices should be connected so that we can call them as smart devices. IoT can be imagined as a wireless network IoT(T,n) in which T denotes the communicating entities in the network and n denotes the data that is to be distributed in between them. The importance of routing in IoT is that each information should be distributed to corresponding devices in the network .This paper is a survey on different protocols through which we can implement the IoT concepts